Phenolics, tannins, flavonoids and anthocyanins contents influenced antioxidant and anticancer activities of Rubus fruits from Western Ghats, India - Kasipandi Muniyandi; Elizabeth George; Saikumar Sathyanarayanan; Blassan P. George; Heidi Abrahamse; Suman Thamburaj; Parimelazhagan Thangaraj (Food Science and Human Wellness)
Rubus fruits are rich in nutrition with a wide range of phytochemical and consumed by humans, but many of its wild varieties are not commercially useful. Phytochemical exploration of these wild fruits could improve the commercial usage of these Rubus species.This study focuses to analyze the phytochemical, antioxidant and cytotoxicity of three wild Rubus ellipticus, R. niveus and R. fairholmianus fruits comparatively, which has not revealed. The in vitro antioxidant studies indicated the ethyl acetate and methanol extracts of studied Rubus species competent in scavenging different stable and generated radical. The correlation and regression analysis also statistically supported the contents in the extracts could act against various radicals. Correlation between phytochemical constituent and radical scavenging activity found to be highly positive. The results acquired from this investigation revealed that they are equally competent and could be recommended as dietary supplements or as nutraceuticals. Keywords: Anticancer, Antioxidant, Flavonoids, Nutraceuticals, Phenolics